2014
DOI: 10.1177/0743558414546717
|View full text |Cite
|
Sign up to set email alerts
|

Newcomer Immigrant Adolescents and Ambiguous Discrimination

Abstract: Cognitive appraisal has been shown to mediate the relationship between stressors and internalizing symptoms, but not among newcomer immigrant youth facing ambiguous discrimination. Using a mixed-methods design with a sample of newcomer adolescents from African, Arab, Asian, Caribbean, European, and Latin American countries, this study measured the perceived occurrence of discrimination (attribution to discrimination) and its perceived degree of severity (cognitive appraisal) in relation to internalizing sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Such appraisals are in turn related to numerous factors, including perception of attribution. A study of immigrant minority youth, including Caribbean youth, demonstrated that cognitive appraisal mediated the relationship between attribution to discrimination and internalizing conditions 49 . There may be difference among Afro Caribbean and African American youth in discrimination attribution and cognitive appraisal of events based on differences in context as well as differences in styles of ethnic and racial socialization—the way youth are taught attitudes and approaches to living in a socially stratified society where discrimination is a reality 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Such appraisals are in turn related to numerous factors, including perception of attribution. A study of immigrant minority youth, including Caribbean youth, demonstrated that cognitive appraisal mediated the relationship between attribution to discrimination and internalizing conditions 49 . There may be difference among Afro Caribbean and African American youth in discrimination attribution and cognitive appraisal of events based on differences in context as well as differences in styles of ethnic and racial socialization—the way youth are taught attitudes and approaches to living in a socially stratified society where discrimination is a reality 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large-scale panel study on discrimination in Germany, more than a third of participants, aged 14 and above, reported encountering discrimination based on factors such as their ethnic origin, gender, disability, religion or world view, age, or sexual identity (Beigang et al, 2016). Exposure to discrimination, both experienced and perceived, has been identified as a risk factor to the well-being of refugee youth in studies in Europe, North America, and Australia (Brough et al, 2003;Ellis et al, 2008Ellis et al, , 2010Fazel et al, 2012;Hassan et al, 2016;Montgomery & Foldspang, 2008;Patel et al, 2014;Shakya et al, 2010). A study in Denmark found that middle Eastern refugee youth reported on average 1.8 experiences of discrimination since having arrived in the country up to 3 years before (Montgomery & Foldspang, 2008).…”
Section: Challenges For Refugee Youthmentioning
confidence: 99%
“…This body of work has focused on the role of family relationships (Kosner, Roer-Strier, & Kurman, 2014; Qin, Chang, Han, & Chee, 2012; Schachner et al, 2014), peers (Fandrem, Ertesvag, Strohmeier, & Roland, 2010; Qin, Way, & Mukherjee, 2008; Walsh, Harel-Fisch, & Fogel-Grinvald, 2010), parents and teacher (Walsh et al, 2010), perceived discrimination (J. Li, 2009; Patel, Tabb, Strambler, & Eltareb, 2015; Vedder, Sam, & Liebkind, 2007), peer victimization (McKenney, Pepler, Craig, & Connolly, 2006), differing expectations between home and school (J. Li, 2009; Qin, 2009), happiness (Neto & Pinto, 2010), gender (Kwak & Rudmin, 2014; Qin, 2006; Suárez-Orozco & Qin, 2006), age (Kwak & Rudmin, 2014), meaning of life (Pan, Wong, Chan, & Joubert, 2008), lifestyle and values of the host culture (Montaruli, Bourhis, Azurmendi, & Larranaga, 2011), ethnic identity and language proficiency (Pfafferott & Brown, 2006; Vedder & Virta, 2005), and social contact and friendship (Zhang & Brunton, 2007) on immigrant adolescents’ adaptation (Kosner et al, 2014; Patel et al, 2015).…”
mentioning
confidence: 99%
“…Li, 2009; Patel, Tabb, Strambler, & Eltareb, 2015; Vedder, Sam, & Liebkind, 2007), peer victimization (McKenney, Pepler, Craig, & Connolly, 2006), differing expectations between home and school (J. Li, 2009; Qin, 2009), happiness (Neto & Pinto, 2010), gender (Kwak & Rudmin, 2014; Qin, 2006; Suárez-Orozco & Qin, 2006), age (Kwak & Rudmin, 2014), meaning of life (Pan, Wong, Chan, & Joubert, 2008), lifestyle and values of the host culture (Montaruli, Bourhis, Azurmendi, & Larranaga, 2011), ethnic identity and language proficiency (Pfafferott & Brown, 2006; Vedder & Virta, 2005), and social contact and friendship (Zhang & Brunton, 2007) on immigrant adolescents’ adaptation (Kosner et al, 2014; Patel et al, 2015). In addition, research on immigrants has also explored strategies for academic achievement (Liebkind, Jasinskaja-Lahti, & Solheim, 2004; Suárez-Orozco et al, 2010; Suárez-Orozco, Rhodes, & Milburn, 2009), life satisfaction (Abu-Laban & Abu-Laban, 1999; Oppedal, Røysamb, & Sam, 2004; Paterson & Hakim-Larson, 2012), sociocultural, psychological (Abu-Rayya, 2014; Tong, 2014; Vedder et al, 2007; Yeh et al, 2005), cross-cultural (Kuo & Roysircar, 2006), and successful adaptation strategies (Dimitrova, Chasiotisa, Bendera, & van de Vijvera, 2014; Lara, 2014; Mancini & Bottura, 2014; Schiefer, Möllering, & Daniel, 2012).…”
mentioning
confidence: 99%